2019
DOI: 10.3390/f10090726
|View full text |Cite
|
Sign up to set email alerts
|

Black Alder (Alnus glutinosa (L.) Gaertn.) on Compacted Skid Trails: A Trade-off between Greenhouse Gas Fluxes and Soil Structure Recovery?

Abstract: The compaction of forest soils can deteriorate soil aeration, leading to decreased CH4 uptake and increased N2O efflux. Black alder (Alnus glutinosa) may accelerate soil structure regeneration as it can grow roots under anaerobic soil conditions. However, symbiotic nitrogen fixation by alder can have undesirable side-effects on greenhouse gas (GHG) fluxes. In this study, we evaluated the possible trade-off between alder-mediated structure recovery and GHG emissions. We compared two directly adjacent 15-year ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 77 publications
0
13
0
1
Order By: Relevance
“…These studies demonstrate that in the evaluation of skid trail recovery, it is prudent to measure multiple soil properties to ascertain if the recovery is complete. Another aspect of skid trail recovery that has received less attention than physical properties is the rehabilitation of chemical properties (Ebeling et al 2017;Neaves et al 2017;Ilintsev et al 2018;Warlo et al 2019;Sohrabi et al 2020). In Malaysia, Malmer et al (1998) encountered contrasting results in two skid trails that were in close proximity to each other (500 m).…”
Section: Soil Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrate that in the evaluation of skid trail recovery, it is prudent to measure multiple soil properties to ascertain if the recovery is complete. Another aspect of skid trail recovery that has received less attention than physical properties is the rehabilitation of chemical properties (Ebeling et al 2017;Neaves et al 2017;Ilintsev et al 2018;Warlo et al 2019;Sohrabi et al 2020). In Malaysia, Malmer et al (1998) encountered contrasting results in two skid trails that were in close proximity to each other (500 m).…”
Section: Soil Recoverymentioning
confidence: 99%
“…Recent studies continue to demonstrate this amelioration effect in these challenging reforestation environments caused by skid trails. For example, the 1 to 6 cm soil depth of skid trails in Southern Germany, Warlo et al (2019) encountered recovery of bulk density, macro and total porosity in wheel tracks after 15 years in a plantation of black alder (Alnus glutinosa) when compared with untrafficked soil. In Switzerland, Meyer et al (2014b) evaluating this same species found no impediments to root penetration even though skid trail penetration resistance values exceeded 2.5 MPa, which is the threshold for reduced root growth (Greacen and Sands 1980).…”
Section: Biological Tillagementioning
confidence: 99%
“…Finally, we examined the 30 remaining studies applying the following inclusion criteria: i) the study must provide a control treatment which consists of soil not affected by machine passage located close to the analysed skid trail/strip road; ii) the experiment must be set up in a forest stand, nursery studies are also included but they have to be clearly related to a forest context. With these criteria, 19 papers (DeArmond et al, 2022;Ebeling et al, 2017;Flores Fernández, Rubin, et al, 2019;Högberg & Wester, 1998;Jourgholami, Ghassemi, & Labelle, 2019;Jourgholami, Ramineh, et al, 2019;Malo & Messier, 2011;Meyer et al, 2014;Rygiewicz et al, 2004;Schäffer, 2022;Schäffer et al, 2009;Stutz et al, 2017;Sugai et al, 2020;Warlo et al, 2019Warlo et al, , 2022Watson & Kelsey, 2006) that generated 217 couple comparisons were finally included in the database for the meta-analysis (Figure 1).…”
Section: Literature Search Studies Inclusion Criteria and Database Bu...mentioning
confidence: 99%
“…The observed N 2 O concentration profiles at this plot, however, did not show strong gradients and possible emissions or consumption could not be calculated. The N 2 O balance of a forest or agricultural site rather depends on catching the peak events [113,114], than spanning the potentially long time between the peak events when fluxes might be negligible. A regular schedule might thus be a drawback.…”
Section: Typical Soil Gas Profilesmentioning
confidence: 99%